Global Trends in Tax Incentives Research: A Bibliometric and Network Analysis - Umikalsom Mohamed Ariffin; Suhaila Abdul Hamid; Izlawanie Muhammad (Global Academic Excellence (M) Sdn Bhd, 2026)
Indexed by MyCite